29 Multi-disciplinary palliative care for men living with duchenne: a qualitative interview study. Issue 3 (1st September 2018) - Laidlaw, Sheonad; Carduff, Emma
Abstract : Background: Duchenne muscular dystrophy (DMD) is an x-linked ultra-rare neuromuscular condition affecting 1 in 3600–6000 live male births. 1 Individuals live with an exceptional illness trajectory of prolonged dwindling frailty and high symptom burden. 2 While it is recognised that a co-ordinated multidisciplinary team approach may increase the survival of those with DMD and improve their quality of life (QoL) 3 adults are receiving less comprehensive and co-ordinated care compared with those in the paediatric service. 4 Aim: To investigate QoL in adults with DMD living in the West of Scotland (WoS). Methods: The SEIQoL-DW tool was used to assess the five most important elements that contribute to an individual's QoL – these were then used to guide qualitative interviews with six men in the WoS. A thematic analysis was undertaken. Results: Men living with DMD in the WoS described living good lives but feel 'forgotten' due to perceived gaps in their care: poorly co-ordinated and infrequent health care; lack of multi-disciplinary team input and holistic care; and poor or no access to allied health care professionals for example physiotherapy and psychological support. Conclusions: Existing guidelines rarely seem materialise as person-centred care. There are numerous opportunities to introduce palliative care gently as part of the MDT early in the illness trajectory and continue in a dynamic manner as time elapses and when trigger points arise. Better co-ordinated multi-disciplinary care with the inclusion of a palliative care specialist may be a solution allowing for an early introduction to palliative care and proactive advance care planning. References: . Bushby K, et al. Diagnosis and management of duchenne muscular dystrophy part 1: Diagnosis and pharmacological and psychosocial managment. Lancet Neurol2010;9:77–93. . Landfeldt E, et al. The burden of duchenne muscular dystrophy. Neurology2014;83:529–36. . Bushby K, et al. Diagnosis and management of duchenne muscular dystrophy part 2: Implementation of multidisciplinary care. Lancet Neurol2010;9:177–89. . Rodger S, et al. Adult care for duchenne muscular dystrophy in the UK. J Neuro2015;262:629–41.